Hubungan Ketidakpuasan Tubuh dan Gangguan Makan dengan Status Gizi Mahasiswa : Relationship between Body Dissatisfaction and Eating Disorders with Nutritional Status of College Students - Dyah Ayu Kusuma Wardani; Dewi Kusumawati; Budi Prasetyo (UNIVERSITAS NGUDI WALUYO, 2025)
Nutritional status is condition of body as a result of the use and absorption of food. National prevalence of nutritional status was underweight 9,3%, normal 55,3%, overweight 13,6% and obese 21,8%. Body dissatisfaction plays a role in development of eating disorders. Eating disorders are characterized by changes in poor eating behavior, negative perceptions about body shape and inappropriate weight management. Aim of this study was to analyze relationship between body dissatisfaction and eating disorders with nutritional status of college students. Design used was cross sectional. Sample in this study was 117 college students at Kusuma Husada University, Surakarta taken using purposive sampling technique. Body dissatisfaction was measured using contour drawing rate scale (CDRS), eating disorders using 26-item eating attitude test (EAT-26) and nutritional status using body mass index (BMI). Data analysis used chi square and Fisher's exact tests. Results of analysis showed that most respondents felt dissatisfied with bodies (90,6%). Most respondents were not at risk of eating disorders (7,5%). Most respondents had normal nutritional status (54,7%). There was no relationship between body dissatisfaction and nutritional status (p=0,752). Although, there was relationship between eating disorders and nutritional status (p=0,037). Conclusion in this study was that there was relationship between eating disorders and nutritional status, however there was no relationship between body dissatisfaction and the nutritional status of college students. ABSTRAK Status gizi adalah keadaan tubuh sebagai akibat dari pemakaian, penyerapan, dan penggunaan makanan. Prevalensi status gizi secara nasional adalah kurus 9,3%, normal 55,3%, berat badan lebih 13,6% dan obesitas 21,8%. Ketidakpuasan tubuh memiliki peran dalam perkembangan gangguan makan. Gangguan makan ditandai dengan perubahan perilaku makan menjadi kurang baik, persepsi negatif tentang bentuk tubuh dan pengaturan berat badan yang kurang tepat. Tujuan penelitian ini adalah untuk menganalisis hubungan ketidakpuasan tubuh dan gangguan makan dengan status gizi mahasiswa. Desain yang digunakan adalah cross sectional. Sampel pada penelitian ini sebanyak 117 mahasiswa di Universitas Kusuma Husada Surakarta yang diambil dengan teknik quota sampling. Ketidakpuasaan tubuh diukur dengan contour drawing rate scale (CDRS), gangguan makan dengan eating attitude test 26 item (EAT-26) dan status gizi dengan indeks massa tubuh (IMT). Analisis data menggunakan uji chi square. Hasil analisis menunjukkan sebagian responden merasa tidak puas dengan tubuhnya (90,6%). Sebagian besar reponden tidak berisiko mengalami gangguan makan (73,5%). Sebagian besar responden memiliki status gizi normal (54,7%). Tidak ada hubungan ketidakpuasan tubuh dengan status gizi mahasiswa (p=0,752). Ada hubungan gangguan makan dengan status gizi mahasiswa (p=0,037). Kesimpulan dalam penelitian ini adalah ada hubungan gangguan makan dengan status gizi namun tidak ada hubungan ketidakpuasan tubuh dengan status gizi mahasiswa.